Ecoliteracy of Junior High School Students in Science Lesson on Environmental Pollution Theme - Sri Paryanti; Indarini Dwi Pursitasari; Bibin Rubini (Scientiae Educatia: Jurnal Pendidikan Sains, 2021)
The low ecoliteracy of students impacts students' low awareness of the environment. This study aims to analyze the ecoliteracy profile of junior high school students. This research is a descriptive study conducted on the seventh-grade students of junior high school with a total of 80 students consisting of 33 male students and 47 female students with purposive sampling. The instrument used in this study was an ecoliteracy test in the form of multiple choice and 20 essay questions. The data collected was analyzed descriptively quantitatively by calculating the percentage of students' acquisition of ecoliteracy and then categorized. The results showed that the average ecoliteracy of students was 50%. The average addition of ecoliteracy on each indicator knows environmental problems (75%), having an action strategy on environmental problems (50%), following up on environmental problems that occur (45%), and having quality in responding to environmental problems and personal attitudes good at 30%. This proves that the level of student ecoliteracy is still relatively low, and efforts need to be made to increase ecoliteracy in students.